Políticas públicas ambientais: aspectos de gerenciamento ambiental para uma análise dos modelos de regulação além do comando e controle - Silva Júnior, Luiz Francisco Tavares da (2014)
The purpose of this work is to treat environmental public policy from a complex vision of its interactions, about the subjects involved and the diversity of interests that they lead to the discussion of environmental issues, as well as of the institutional arrangements regarding the instruments of public action. It also puts in discussion on some regulatory instruments rather than command-and-control approach, proposing a combination of these models in the implementation of environmental public policies. From this point, it searches the practical exam of a public environmental policy, the management of contaminated areas, in a critical analysis of its organisation and implementation, restricting the analytical spectrum in the State of São Paulo in Brazil